BREAST STEM CELLS AND THEIR PARTICIPATION IN CARCINOGENESIS - Чайковський, Ю. Б.; Дєльцова, О. І.; Геращенко, С. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The results of contemporary researches of breast stem cells are considered in the article. Cogent arguments for the presence of three types of progenitor cells – for myoepithelial cells, epithelium of ducts and epithelial cells of mammary gland are given. Their role in the origin of breast cancer is discussed.